Challenges Of KUA In Implementing Pre-Marriage Guidance As an Effort To Build Sakinah Families In Medan City - Auliya, Siti; Daulay, Harmona; Elida, Linda (The Islamic Education and Multiculturalism Foundation, 2025)
AbstrakPeran bimbingan perkawinan pranikah sesuai dengan tujuan pernikahan yaitu untuk mewujudkan keluarga sakinah mawaddah warrahmah sesuai dengan ajaran agama Islam. Bimwin sebagai upaya meningkatkan kualitas kehidupan keluarga yang harmonis. Pelaksanaan bimbingan perkawinan di Kantor KUA khususnya di Kota Medan memiliki tantangan dari masyarakat, kurangnya kesadaran akan pentingnya mengikuti bimbingan perkawinan dan menganggap pelaksanaan bimbingan perkawinan hanya sebagai pelengkap administrasi pernikahan. Adapun tujuan penelitian ini adalah untuk mengetahui tantangan KUA dalam pelaksanaan bimbingan perkawinan dan upaya KUA dalam mewujudkan keluarga sakinah di Kota Medan. Metode penelitian ini pendekatan kualitatif. Hasil penelitian menunjukan bahwa Bimbingan perkawinan di Kantor Urusan Agama di kota Medan berfungsi sebagai penyampai informasi penting untuk para calon pengantin melalui materi dan fasilitator yang disampaikan, khususnya informasi tentang pentingnya memiliki dasar pengetahuan agama bagi pasangan suami isteri, juga persiapan sebagai orangtua dalam mendidik anak-anak dengan dasar agama. Bimbingan perkawinan bermanfaat untuk pasangan pengantin dalam membangun masa depan yang lebih terarah, mengurangi risiko keretakan hubungan, memudahkan dalam penyatuan visi dan saling memahami keluarga pasangan.Kata Kunci: Kantor Urusan Agama, Bimbingan Perkawinan, Pelaksanaan AbstractThe role of premarital marriage guidance is in accordance with the purpose of marriage, namely to realize a harmonious family, mawaddah, warrahmah, in accordance with Islamic teachings. Bimwin as an effort to improve the quality of harmonious family life. The implementation of marriage guidance at the KUA Office, especially in Medan City, has challenges from the community, lack of awareness of the importance of following marriage guidance and considering the implementation of marriage guidance only as a complement to marriage administration. The purpose of this study was to determine the challenges of the KUA in implementing marriage guidance and the efforts of the KUA in realizing a harmonious family in Medan City. This research method is a qualitative approach. The results of the study showed that marriage guidance at the Religious Affairs Office in Medan City functions as a conveyor of important information for prospective brides and grooms through the materials and facilitators presented, especially information about the importance of having a basic knowledge of religion for married couples, as well as preparation as parents in educating children with a religious basis. Marriage guidance is useful for couples in building a more focused future, reducing the risk of relationship breakdown, facilitating the unification of visions and understanding each other's families.Keywords: Office of Religious Affairs, Marriage Guidance, Implementation